Prevalence and Predictive Factors of Histopathological Complications in Children with Esophageal Atresia - Petit, Laetitia-Marie; Righini-Grunder, Franziska; Ezri, Jessica; Jantchou, Prevost; Aspirot, Ann; Soglio, Dorothée Dal; Faure, Christophe (European Journal of Pediatric Surgery, 2019)
Objectives Endoscopic follow-up after esophageal atresia (EA) tracheoesophageal fistula (TEF) repair is recommended to detect esophageal histopathological complications. We investigated the prevalence of histopathologically proven esophageal complications (peptic esophagitis, gastric metaplasia, and eosinophilic esophagitis) and assessed the predictors of these complications in children with EA-TEF.Materials and Methods This is a prospective longitudinal cohort study performed between September 2005 and December 2014 comprising 77 children with EA-TEF followed-up until February 2017. Univariate analysis was performed using the Wilcoxon's rank-sum test for continuous variables and the Pearson's chi-square test for categorical variables. Multivariable analysis was performed using a Cox regression hazard model. The association between clinical factors and histopathologically proven complications was estimated using a Cox regression hazard model with time until the appearance of complications as the time scale.Results All 77 children received proton pump inhibitors (PPIs) (n = 73) or H2 receptor antagonists (H2RA). A total of 252 endoscopies were performed in 73 children (median 2.6/child, range: 1–29). Median age at study completion was 4.9 years (range: 2.3–11.5 years). Histopathologically proven complications occurred in 38 children (52%): peptic esophagitis (n = 32, 44%), eosinophilic esophagitis (n = 15, 21%), and gastric metaplasia (n = 9, 12%). A total of 82% patients were on PPI or H2RA at the time of diagnosis of histological complication. Multivariable Cox regression analysis showed that patients with recurrent anastomotic strictures (>3 dilations) had a higher risk of occurrence of histopathologically proven complications over time (hazard ratio: 3.11, 95% confidence interval [CI]: 1.53–6.34). On univariate analysis, the result of the first endoscopy was not associated with the occurrence of histopathologically proven complications (odds ratio: 0.8, 95% CI: 0.16–3.95).Conclusion Histopathologically proven complications with potential long-term consequences occurred in approximately 50% of children after EA-TEF repair. A history of recurrent anastomotic strictures is associated with the occurrence of these complications. The result of the first endoscopy does not predict the histopathological outcome. Children with EA-TEF warrant close and systematic long-term follow-up at specialized multidisciplinary clinics with endoscopic evaluation.
Keywords: esophageal atresia; esophagitis; eosinophilic esophagitis; acid reflux; endoscopy